Engaging Frontline Providers Prevents Hypothermia and Improves Communication in the Postoperative Neonate. (October 2021) - Guidash, Judith C.; Berman, Loren; Panagos, Patoula G.; Sullivan, Kevin M.
Abstract : Background: Neonates undergoing surgery are at high risk for perioperative hypothermia. Hypothermia has been associated with increased adverse events. Transfer of care from the operating room (OR) to the neonatal intensive care unit (NICU) adds another layer of risk for this population introducing the potential for miscommunication leading to preventable adverse events. Purpose: The aim of this quality improvement initiative is to decrease mean postoperative hypothermia rate and achieve compliance with use of a standardized postoperative hand-off in neonates transferred to the NICU from the OR. Methods: An interdisciplinary team identified opportunities for heat loss during the perioperative period. The lack of standardized perioperative communication between the NICU and the OR and postoperative communication between neonatology, anesthesiology, surgery, and nursing were noted. Guidelines for maintaining euthermia in the perioperative period and a standardized interdisciplinary postoperative hand-off communication tool were created. Findings/Results: Mean rate for participation in the hand-off process increased from 78.8% to 98.4% during the study period. The mean hypothermia rate improved from 28.6% to 6.3% ( P < .0001) and was sustained. Implications for Practice: Creating a hypothermia guideline and standardizing temperature monitoring can significantly decrease the rate of postoperative hypothermia in neonates. Standardization of transfer of care from OR to NICU increases consistent communication between the services. Implications for Research: Future research and improvement efforts are needed to optimize the management of surgical neonates through their transfers of care. Abstract : Supplemental Digital Content is Available in the Text.